Rapid thermal annealing for high-quality ITO thin films deposited by radio-frequency magnetron sputtering - Prepelita, Petronela; Stavarache, Ionel; Craciun, Doina; Garoi, Florin; Negrila, Catalin; Sbarcea, Beatrice Gabriela; Craciun, Valentin (Beilstein Journal of Nanotechnology, 2019)
In this work, rapid thermal annealing (RTA) was applied to indium tin oxide (ITO) films in ambient atmosphere, resulting in significant improvements of the quality of the ITO films that are commonly used as conductive transparent electrodes for photovoltaic structures. Starting from a single sintered target (purity 99.95%), ITO thin films of predefined thickness (230 nm, 300 nm and 370 nm) were deposited at room temperature by radio-frequency magnetron sputtering (rfMS). After deposition, the films were subjected to a RTA process at 575 °C (heating rate 20 °C/s), maintained at this temperature for 10 minutes, then cooled down to room temperature at a rate of 20 °C/s. The film structure was modified by changing the deposition thickness or the RTA process. X-ray diffraction investigations revealed a cubic nanocrystalline structure for the as-deposited ITO films. After RTA, polycrystalline compounds with a textured (222) plane were observed. X-ray photon spectroscopy was used to confirm the beneficial effect of the RTA treatment on the ITO chemical composition. Using a Tauc plot, values of the optical band gap ranging from 3.17 to 3.67 eV were estimated. These values depend on the heat treatment and the thickness of the sample. Highly conductive indium tin oxide thin films (ρ = 7.4 × 10−5 Ω cm) were obtained after RTA treatment in an open atmosphere. Such films could be used to manufacture transparent contact electrodes for solar cells.
Keywords: conductive transparent electrodes; indium tin oxide (ITO) films; optical properties; radio-frequency magnetron sputtering (rfMS); rapid thermal annealing (RTA)